2018
DOI: 10.1002/jctb.5664
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up and economic analysis of the production of ligninolytic enzymes from a side‐stream of the organosolv process

Abstract: BACKGROUND Organosolv pretreatment produces a hemicellulose‐rich stream with limited applications due to its toxicity. In this study, beech wood organosolv liquor was valorized through the production of ligninolytic enzymes, the extraction of ganoderic acid and the detoxification of this process stream. RESULTS Laccase and manganese peroxidase (MnP) were produced in 30 L bioreactors by the white‐rot fungi Ganoderma lucidum and Irpex lacteus, respectively, using the hemicellulose‐rich liquor as carbon source. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As can be seen in Fig. 2 , the use of peptone stimulated enzyme production (Lú-Chau et al 2018 ; Pinheiro et al 2020 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As can be seen in Fig. 2 , the use of peptone stimulated enzyme production (Lú-Chau et al 2018 ; Pinheiro et al 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…4 , before the onset of enzyme production, the pH value decreased to around 4.4 and after the peak of MnP production, the pH increased again. On the other hand, the redox potential underwent an increase as more enzyme was produced, reaching its maximum value (500 mV) in parallel to the peak of enzyme production (Lú-Chau et al 2018 ). Another remarkable fact is that enzyme production started once the glucose concentration was below 0.8 g/L, similar to the trend observed in Erlenmeyer flask experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that in solid state cultivation under optimized conditions, it was possible to produce laccase at laboratory scale, with a final price of 0.04 cent € per unit. More recently, laccase from the white-rot fungus Ganoderma lucidum was produced in 30 L bioreactors using the hemicellulose-rich liquor as carbon source (Lú-Chau et al, 2018). Economic analysis of the latter process resulted in a € 1.08 kU − 1 (0.01 cent € per unit).…”
Section: Bottlenecks and Perspectivesmentioning
confidence: 99%
“…Most recently, the same strategy was adopted by [50] for the production of laccase from Ganoderma lucidum in 30 L bioreactors. The authors used the hemicellulose-rich, beechwood organosolv pretreatment stream as a growth medium for the cultivation and obtained up to 596 U L −1 of laccase activity.…”
Section: Production Of Laccasesmentioning
confidence: 99%